2012
DOI: 10.1016/j.neulet.2012.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin receptor stimulation of the medial nucleus accumbens differentially affects appetitive motivation for food on a progressive ratio schedule of reinforcement

Abstract: Previously, we reported that stimulation of selective serotonin (5-HT) receptor subtypes in the nucleus accumbens shell differentially affected consumption of freely available food. Specifically, activation of 5-HT6 receptors caused a dose-dependent increase in food intake, while the stimulation of 5-HT1/7 receptor subtypes decreased feeding [34]. The current experiments tested whether similar pharmacological activation of nucleus accumbens serotonin receptors would also affect appetitive motivation, as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…This suggests that the antidepressant effects of these compounds are, at least in part, due to long-term cellular adaptations downstream, and perhaps far removed, from increased serotonin signaling. Multiple subtypes of serotonin receptors are expressed in NAc, including 5-HT 1/7 , 5-HT 2C , and 5-HT 6 receptors, and NAc-specific pharmacological manipulation of these individual receptor types alters multiple behaviors, including feeding (Pratt et al, 2012) and alcohol action (Andrade et al, 2011). Although the mechanisms that link increased serotonin signaling to epigenetic modifications at the CaMKIIa promoter remain virtually completely unknown, we have demonstrated previously that chronic, systemic administration of fluoxetine or chronic NAcspecific inhibition of histone deacetylases-both of which produce antidepressant-like behavioral actions-have strikingly similar effects on global patterns of gene expression in NAc .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the antidepressant effects of these compounds are, at least in part, due to long-term cellular adaptations downstream, and perhaps far removed, from increased serotonin signaling. Multiple subtypes of serotonin receptors are expressed in NAc, including 5-HT 1/7 , 5-HT 2C , and 5-HT 6 receptors, and NAc-specific pharmacological manipulation of these individual receptor types alters multiple behaviors, including feeding (Pratt et al, 2012) and alcohol action (Andrade et al, 2011). Although the mechanisms that link increased serotonin signaling to epigenetic modifications at the CaMKIIa promoter remain virtually completely unknown, we have demonstrated previously that chronic, systemic administration of fluoxetine or chronic NAcspecific inhibition of histone deacetylases-both of which produce antidepressant-like behavioral actions-have strikingly similar effects on global patterns of gene expression in NAc .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Jean et al (2007) reported that the 5-HT 4 receptor in the mouse nucleus accumbens is responsible for the hypophagic actions of systemic MDMA (Ecstasy) treatment. We have reported that stimulation of rat medial nucleus accumbens 5-HT 6 receptors increases food intake and enhances appetitive motivation for sugar reinforcement (Pratt et al , 2009, Pratt et al , 2012). In contrast, nucleus accumbens 5-HT 2C receptor agonism or blockade has little effect on food motivation.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, the roles of multiple neurotransmitter systems within the NAcc have been characterized, demonstrating important roles for glutamate [58-60], GABA [61-63], dopamine [64], opioids [36, 52-54], acetylcholine [28, 65-67], and serotonin [68-71] receptors on appetitive and consummatory behaviors directed towards food. Though both adenosine and opioid systems of the NAcc have previously been shown to impact food intake, this is the first examination of the potential roles for A2A and μ-opioid receptors of this region on the learning of an operant response reinforced by food.…”
Section: Discussionmentioning
confidence: 99%